Analysis Intellectual Capital of Corporate Value at Indonesia Stock Exchange (Economic and Bussiness Faculty, Dr Soetomo University, 2020)
This study examines the effect of intellectual capital on firm value. Methods of data collection with documentation data in the form of financial reporting Companies listed on the Indonesia Stock Exchange, 2014 to 2016. Data processed was 84 companies. Analysis of research data using quantitative with linear regression. Intellectual variable is measured with value added, variable of company value measured by Tobins Q. The result of this research intellectual capital have an effect on company value.